Stem cell tools and other experimental protocols - Klimanskaya, Irina; Lanza, Robert, 1956- (Methods in enzymology, 2006)
This is the third of three planned volumes in the Methods in Enzymology series on the topic of stem cells. This volume is a unique anthology of stem cell techniques written by experts from the top laboratories in the world. The contributors not only have hands-on experience in the field but often have developed the original approaches that they share with great attention to detail. The chapters provide a brief review of each field followed by a "cookbook" and handy illustrations